Repeated infusion of mesenchymal stem cells maintain the condition to inhibit deteriorated motor function, leading to an extended lifespan in the SOD1G93A rat model of amyotrophic lateral sclerosis - Hirotoshi Magota; Masanori Sasaki; Yuko Kataoka-Sasaki; Shinichi Oka; Ryo Ukai; Ryo Kiyose; Rie Onodera; Jeffery D. Kocsis; Osamu Honmou (Molecular Brain, 2021)
Abstract Amyotrophic lateral sclerosis (ALS) is a neurodegenerative fatal disorder in which motor neurons within the brain and spinal cord degenerate. A single infusion of mesenchymal stem cells (MSCs) delays disease progression by protecting motor neurons and restoring the blood-spinal cord barrier in the SOD1G93A transgenic ALS rat model. However, the therapeutic effect of a single infusion of MSCs is transient and does not block disease progression. In this study, we demonstrated that repeated administration of MSCs (weekly, four times) increased the survival period, protected motor functions, and reduced deterioration of locomotor activity compared to a single infusion and vehicle infusion, after which rats displayed progressive deterioration of hind limb function. We also compared the days until gait ability was lost in rats and found that the repeated-infused group maintained gait ability compared to the single-infusion and vehicle-infusion groups. These results suggest that repeated administration of MSCs may prevent the deterioration of motor function and extend the lifespan in ALS.